Prospective Associations of the Short Form Health Survey Vitality Scale and Changes in Body Mass Index and Obesity Status - Cathrine Lawaetz Wimmelmann; Emilie Rune Hegelund; Anna Paldam Folker; Emilie Just-Østergaard; Merete Osler; Erik Lykke Mortensen; Trine Flensborg-Madsen (Hindawi Limited, 2018)
Objectives. The objectives of the current study were to prospectively investigate the predictive value of the vitality scale of the Short Form Health Survey for changes in body mass index and development of obesity. Methods. The study population comprised 2864 (81.5%) men and 648 (18.5%) women from the Metropolit Project and the Danish Longitudinal Study on Work, Unemployment and Health, who participated in a follow-up examination in 2009-2011 corresponding to a follow-up period of 3-7 years. Associations of vitality with body mass index and obesity were investigated separately for men and women in linear and logistic regression models adjusting for age, baseline body mass index, education, physical activity, smoking, and obesity-related diseases. Results. Vitality was significantly associated with change in body mass index among men (p<0.001) and women (p<0.05) gaining weight after adjusting for age, baseline body mass index, education, physical activity, smoking, and obesity-related diseases. No significant associations of vitality with BMI change were observed among individuals maintaining or losing weight during the follow-up period. Furthermore, vitality significantly predicted development of obesity among women. Conclusion. The study indicates that vitality is of predictive value for increases in BMI over time among individuals gaining weight and may further predict the development of obesity among women. This identification of poor vitality as a potential risk indicator for weight gain and development of obesity may be beneficial in clinical practice.